(untitled) (REMUNOM, 2023)
Implantology is a highly sought-after procedure, mainly for aesthetic reasons, but also because most surgeries are successful. However, in some cases, the loss of the implant occurs, being one of the causes the evolution of the so-called peri-implantitis. Peri-implantitis is an inflammatory process of the tissues around osseointegrated implants of multifactorial cause, the primordial ones being the occlusal load and the bacterial plaque formed around the implants. Appropriate treatment consists of preserving a blockage composed of healthy tissues and monitoring the biofilm. The essential precautions are good oral hygiene and avoiding alcohol consumption and smoking. The most accurate diagnosis is by means of periapical radiographs for the confirmation of the pathology of peri-implantitis.